Developing and validating an ICT adoption framework for SMEs in developing countries : a case of Zimbabwe - Steyn, Adriana Aletta (Riana) (University of Pretoria, 2018)
In recent decades, Information and Communication Technology (ICT), adoption in global Small to Medium Enterprises (SMEs), transformed the business landscape and has had a significant effect on social and economic developments that have saturated every aspect of human life. However, SMEs in developing countries are still facing various constraints that inhibit them from effectively incorporating ICT in their business operations and Zimbabwe has not been an exception. This research investigated the main reasons why Zimbabwean SMEs face challenges in adopting and utilising ICT, with particular emphasis on the role of the government in enhancing ICT use in SMEs. The study also aimed at presenting a validated and implementable ICT adoption framework that the Zimbabwean government can utilise to stimulate ICT adoption in SMEs. The methodology adopted in undertaking this research was the Design Science Research (DSR) approach that facilitated the creation of innovative and unique solutions relevant to the issues under study. The approach included a qualitative survey that utilised semi-structured interviews with 12 SMEs in and around five key Zimbabwean cities. The study revealed key government-related factors that affect ICT adoption in Zimbabwean SMEs that facilitated the development of an SME ICT adoption framework. These factors included government policies, government support and financial subsidies. The framework was validated using a focus group approach. The analysed data revealed that the framework is valid and relevant for use in practice, with the majority of the participants accepting and agreeing with the framework constructs. The study also offered various recommended strategies that will aid the government and other key SME stakeholders in resolving the challenges that SMEs face in adopting and utilising ICT.